MEMAKNAI BUNGA DI ATAS BATU Patung Karya Anusapati - Sumarwahyudi Sumarwahyudi (Fakultas Sastra Universitas Negeri Malang, 2014)
Sculpture is an iconic sign to convey a message or something that can be used to represent a state (context), events of the past, or those in the future. Sculpture consists of iconic signs that work together systemically to achieve certain goals. This study aims to (1) describe the meaning of denotation, and (2) interpret the connotative meaning of Anusapati’s work entitled “Bunga di Atas Batu” (Flower on a Stone), a bronze statue created in 2004, by employing the connotative semiotics approach of Roland Barthes. The sculpture portrays a monument, which invites everyone to see that ‘flower’ as the connotation of the forest has been elevated, not to be given a respectable position, but just to be remembered. Forests as valuable assets owned by the Indonesians and even the world are seen metaphorically as ‘the flower’ which is gradually disappearing, (almost) becoming a memory. In some areas in Indonesia, forests have even completely disappeared and only left memories behind